Effect of plasticity on dynamic impact in a journal-bearing system: A planar case. (December 2020) - Peng, Q.; Ye, X.; Wu, H.; Liu, X.; Wei, Y.G.
Highlights: A conformal contact law considering plasticity is implemented into a planar dynamics solver for journal/bearing system. A critical impact speed is proposed for whether the plasticity should be considered or not. When plasticity cannot be ignored, the dynamic prediction with the proposed model can achieve more accurate results. Abstract: Plasticity is inevitable during contact with a high load, and thus should be considered when simulating high-load contact. Plasticity during non-conformal contact has been well studied. However, no contact law that considers plasticity during conformal contact has been developed, even though such ``plastic conformal contact'' commonly occurs in journal-bearing systems under high loads. Herein, we constructed a plastic Winkle model of plastic conformal contact, and integrated it into a contact solver to simulate the impact dynamics of a single journal-bearing system. The plastic contact law was first verified by finite-element simulations, which were in good agreement with the plastic indentation observed during loading and unloading. To study the plasticity during conformal impact, we integrated the contact law into a dynamic-contact model of the single journal-bearing system. The results indicate that the energy dissipation due to plasticity was much greater than that from damping and friction. Ignoring plasticity may result in an unrealistic travel distance of the journal during impact. The developed model was used to construct a velocity map to determine whether or not that plasticity should be considered. Graphic Abstract: Image, graphical abstract